Effects of glufosinate‐ammonium herbicide and pod sealant on spider Pardosa agrestis. (10th October 2018) - Niedobová, Jana; Krištofová, Lucie; Michalko, Radek; Hula, Vladimír; Kýnický, Jindřich; Brtnický, Martin
Abstract: Herbicides based upon glufosinate‐ammonium (GLA) are among the world's most widely used. They also are applied on the most prominent oil crops as desiccants in combination with pod sealants to prevent pod shatter and seed loss close to harvest. Even though these crops occupy a significant part of the world's agroecosystems, the effects of GLA herbicides on non‐target arthropods, and in particular natural enemies of pests, have been studied very rarely, and such effects of pod sealants have never been studied. We studied in our laboratory mortality as well as prey capture efficiency of the common GLA herbicide and desiccant Basta 15 ®, pod sealant Arrest ®, and a mixture of both on the wolf spider Pardosa agrestis . We found that Basta 15 ® and the mixture had lethal effect on spiders. We also found significant, short‐term effect on predatory activity of spiders after all treatments. Basta 15 ® significantly influenced the amount of captured prey also in the long term. This is the first study showing lethal effect on spiders of the herbicide and herbicide plus pod sealant mixture. This is also the first study examining the effects of pod sealant on the mortality and predatory activity of a pest antagonist. More studies regarding the effects of agricultural chemical mixes are needed to uncover their effects on beneficial organisms existing within agroecosystems.